An optimal control model with cost effectiveness analysis of Maize streak virus disease in maize plant - Haileyesus Tessema Alemneh; Assefa Sintayehu Kassa; Anteneh Asmare Godana (Infectious Disease Modelling, 2021)
In this paper we formulated and analyzed an optimal deterministic eco-epidemiological model for the dynamics of maize streak virus (MSV) and examine the best strategy to fight maize population from maize streak disease (MSD). The optimal control model is developed with three control interventions, namely prevention (u1), quarantine (u2) and chemical control (u3). To achieve an optimal control strategy, we used the Pontryagin’s maximum principle obtain the Hamiltonian, the adjoint variables, the characterization of the controls and the optimality system. Numerical simulations are performed using Forward-backward sweep iterative method. The findings show that each integrated strategy is able to mitigate the disease in the specified time. However due to limited resources, it is important to find a cost-effective strategy. Using Incremental Cost-Effectiveness Ratio(ICER) a cost-effectiveness analysis is investigated and determined that the combination of prevention and quarantine is the best cost-effective strategy from the other integrated strategies. Therefore, policymakers and stakeholders should apply the integrated intervention to stop the spread of MSV in the maize population.